Mismatch Repair Status Characterization in Oncologic Pathology: Taking Stock of the Real-World Possibilities - Roberto Piciotti; Konstantinos Venetis; Elham Sajjadi; Nicola Fusco (MDPI AG, 2021)
The mismatch repair (MMR) system has a key role in supporting the DNA polymerase proofreading function and in maintaining genome stability. Alterations in the MMR genes are driving events of tumorigenesis, tumor progression, and resistance to therapy. These genetic scars may occur in either hereditary or sporadic settings, with different frequencies across tumor types. Appropriate characterization of the MMR status is a crucial task in oncologic pathology because it allows for both the tailored clinical management of cancer patients and surveillance of individuals at risk. The currently available MMR testing methods have specific strengths and weaknesses, and their application across different tumor types would require a tailored approach. This article highlights the indications and challenges in MMR status assessment for molecular pathologists, focusing on the possible strategies to overcome analytical and pre-analytical issues.